1991
DOI: 10.1128/aem.57.9.2617-2621.1991
|View full text |Cite
|
Sign up to set email alerts
|

Giardia and Cryptosporidium spp. in filtered drinking water supplies

Abstract: Giardia and Cryptosporidium levels were determined by using a combined immunofluorescence test for ifitered drinking water samples collected from 66 surface water treatment plants in 14 states and 1 Canadian province. Giardia cysts were detected in 17% of the 83 filtered water effluents. Cryptosporidium oocysts, were observed in 27% of the drinking water samples. Overall, cysts or oocysts were found in 39% of the treated effluent samples. Despite the frequent detection of parasites in drinking water, microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
3

Year Published

2001
2001
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(95 citation statements)
references
References 10 publications
2
90
0
3
Order By: Relevance
“…Current routine methods for the enumeration of Cryptosporidium in water are not only inef®cient but also do not provide an indication of which species has been recovered nor of the viability or infectivity of the oocysts. Not surprisingly, most 100±1000 l samples record zero pathogens under non-outbreak conditions (Payment et al 1985;LeChevallier et al 1991). Indeed, LeChevallier et al (1991) reported 73% of 100-l volumes from ®ltered drinking water supplies to contain zero oocysts of Cryptosporidium.…”
Section: Pathogen Exposures Under Non-outbreak Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current routine methods for the enumeration of Cryptosporidium in water are not only inef®cient but also do not provide an indication of which species has been recovered nor of the viability or infectivity of the oocysts. Not surprisingly, most 100±1000 l samples record zero pathogens under non-outbreak conditions (Payment et al 1985;LeChevallier et al 1991). Indeed, LeChevallier et al (1991) reported 73% of 100-l volumes from ®ltered drinking water supplies to contain zero oocysts of Cryptosporidium.…”
Section: Pathogen Exposures Under Non-outbreak Conditionsmentioning
confidence: 99%
“…It is apparent that oocyst densities in drinking water supplies during non-outbreak conditions show large variation. While most samples contain zero oocysts, a few contain high counts (LeChevallier et al 1991). This re¯ects both spatial/temporal variations within different parts of the same supply and systematic differences between different supplies (e.g.…”
Section: Pathogen Exposures Under Non-outbreak Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this study, it was not feasible to concurrently measure source water Cryptosporidium levels for all participating water treatment plants, but previous studies have documented surface water oocyst levels (LeChevallier & Norton, 1995;LeChevallier et al, 1991). Although these results from the studies cited were generated using older techniques that do not match method 1622 results (e.g., they should not be used to establish bin levels required by the LT2ESWTR), the Cryptosporidium levels can be used to rank the relative level of source water pollution.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the published human dose-response data (Messner et al, 2001), it is possible to use the results of the current study to determine the risk of Cryptosporidium infection from conventionally treated drinking water. To calculate the risk, it was necessary to assume that each positive sample was identified as such because of the detection of a single oocyst, because previous IFA studies typically detected a single oocyst in filtered drinking water (LeChevallier et al, 1995;LeChevallier et al, 1991).…”
Section: Figure 4 Fmentioning
confidence: 99%